2011
DOI: 10.1364/ol.36.000385
|View full text |Cite
|
Sign up to set email alerts
|

Light transmission properties of double-overlapped annular apertures

Abstract: We investigate the light transmission properties of double-overlapped annular apertures in a silver film with the three-dimensional finite-difference time-domain method. It has been found that the transmission peaks are attributed to the localized surface plasmon resonance (LSPR) of nanocavities and the surface plasmon polaritons (SPPs) of the nanoparticles. The peaks of the LSPR are blueshifted when the overlapping distance is increased. Moreover, a Fano-type resonance appears in the transmitted spectral resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…In such XI cavities, the coherent near‐field coupling takes place between broad dipole and sharp quadrupole modes being excited in the cross, and excited dipole resonance in the bar . An alternative way to generate FR is by forming nanometric apertures in metallic thin films . Artar et al.…”
Section: Fr Generationmentioning
confidence: 99%
“…In such XI cavities, the coherent near‐field coupling takes place between broad dipole and sharp quadrupole modes being excited in the cross, and excited dipole resonance in the bar . An alternative way to generate FR is by forming nanometric apertures in metallic thin films . Artar et al.…”
Section: Fr Generationmentioning
confidence: 99%
“…1 Numerous nanostructures have been designed to form Fano resonances, such as metamaterials, 2,3 coupled nanoparticles, [4][5][6][7][8] and plasmonic clusters. [9][10][11][12][13] Given their asymmetric line shape, weak radiative damping, and strong sensitivity to the local environment, Fano resonances have been used for slow light, 2 enhanced light transmission, 14 biosensing, 4,15,16 surface enhanced Raman scattering (SERS), 17 and plasmonic switch. 18 In nanostructures with two or more dark subradiant modes, multiple Fano resonances can arise in the spectra, which have been observed in numerous systems such as multilayer oligomers, 19 nanoparticle clusters, [20][21][22][23][24] dual-disk ring cavities, 25 and plasmonic clusters with dielectric particles.…”
mentioning
confidence: 99%
“…In addition, the two-dimensional (2D) symmetric double ring resonators have been studied. It is demonstrated that the band-pass filter with two ring resonators has better sensitivity to the wavelength than one with a single ring resonator [20,21]. However, for the MIM waveguide structure discussed in their work, the two MIM waveguides are symmetrically situated on both sides of the two rings.…”
Section: Introductionmentioning
confidence: 97%